When the peas jump around the pod: how stellar clustering affects the observed correlations between planet properties in multiplanet systems - Chevance, Mélanie; Kruijssen, Diederik; Longmore, Steven N. (The astrophysical journal. Part 2, Letters, 2021)
Recent studies have shown that the radii and masses of adjacent planets within a planetary system are correlated. It is unknown how this “peas-in-a-pod” phenomenon originates, whether it is in place at birth or requires evolution, and whether it (initially) applies only to neighboring planets or to all planets within a system. Here we address these questions by making use of the recent discovery that planetary system architectures strongly depend on ambient stellar clustering. Based on Gaia's second data release, we divide the sample of planetary systems hosting multiple planets into those residing in stellar position-velocity phase space overdensities and the field, representing samples with elevated and low degrees of external perturbation, respectively. We demonstrate that the peas-in-a-pod phenomenon manifests itself in both samples, suggesting that the uniformity of planetary properties within a system is not restricted to direct neighbors and likely already exists at birth. The radius uniformity is significantly elevated in overdensities, suggesting that it can be enhanced by evolutionary effects that either have a similar impact on the entire planetary system or favor the retention of similar planets. The mass uniformity may exhibit a similar, but weaker dependence. Finally, we find ordering in both samples, with the planet radius and mass increasing outwards. Despite its prevalence, the ordering is somewhat weaker in overdensities, suggesting that it may be disrupted by external perturbations arising from stellar clustering. We conclude that a comprehensive understanding of the peas-in-a-pod phenomenon requires linking planet formation and evolution to the large-scale stellar and galactic environment.